1995
DOI: 10.1007/s004410050520
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and morphometric study on the changes of TSH, PRL, GH and ACTH cells during the development of Bufo arenarum

Abstract: The development and dynamics of thyrotropin (TSH), adrenocorticotropic hormone (ACTH), prolactin (PRL), and growth hormone (GH) cells have been studied using immunocytochemical techniques and rabbit antisera, raised against the relevant human hormone, in the pars distalis of Bufo arenarum larvae at different stages of development. The four types of cells studied were identified in different zones of the pars distalis: TSH cells occurred mainly in the centro-ventral zone, ACTH cells in the rostral and dorsal zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Similar results were reported by other authors who have demonstrated that testosterone has an effect on the GH cells [Wehrenberg et al, 1985;Hertz et al, 1989;Kineman et al, 1990]. Investigations carried out in mink [Vidal et al, 1994], B. arenarum [Miranda et al, 1996], Anguilla anguilla L. [Grandi et al, 2003] and pig [Lee et al, 2004] of different ages showed morphometric differences of the somatotrophs probably due to the different physiological stages. In viscacha, the castration provoked a significant decrease in the immunopositive area, in the number of cells and in the major cellular diameter, and when studying the different growth stages, a gradual increase in these parameters was observed in relation to the degree of the testicular activity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were reported by other authors who have demonstrated that testosterone has an effect on the GH cells [Wehrenberg et al, 1985;Hertz et al, 1989;Kineman et al, 1990]. Investigations carried out in mink [Vidal et al, 1994], B. arenarum [Miranda et al, 1996], Anguilla anguilla L. [Grandi et al, 2003] and pig [Lee et al, 2004] of different ages showed morphometric differences of the somatotrophs probably due to the different physiological stages. In viscacha, the castration provoked a significant decrease in the immunopositive area, in the number of cells and in the major cellular diameter, and when studying the different growth stages, a gradual increase in these parameters was observed in relation to the degree of the testicular activity.…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported that in male rats the number of GH cells varies according to the presence of gonadal steroids during the neonatal period [González-Parra et al, 1998. Moreover, the relationship between the somatotrophs and animals growth stages or age was studied in Bufo arenarum [Miranda et al, 1996] and pig [Lee et al, 2004]. Jurado et al [1998] demonstrated that the GH cell area and perimeter decreased in old rats as compared to young animals, suggesting that aging affects the immunohistochemical and ultrastructural features of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…100, where ⌺ Ac was the sum of the area of immunolabelled cells for anti-␣ -MSH and ⌺ RA was the sum of the PI area of every microscopic field. The percentage of immunopositive area represents the volume density, and it was calculated according to the concept usually accepted and used by several authors [Miranda et al, 1996;Cónsole et al, 2001;Mohamed, 2006b, 2008].…”
Section: Melanotrophsmentioning
confidence: 99%
“…In addition to these antisera we used a prediluted rabbit anti-hTSH antiserum, L1842 (DAKO A/S, code L1842), reported by DAKO to be specific for hTSH. This antiserum has recently been characterized and used for immunocytochemical studies in Bufo arenarum (Miranda et al 1996). Finally we included an antiserum raised in rabbit against ovine TSH-S8 (kindly donated by NIAMDD) as previously described (Hansen 1983).…”
Section: Antiseramentioning
confidence: 99%